IMPOLITENESS STRATEGIES IN THE YOUTUBE COMMENT SECTION - Adinda Siti Nuralia; Agus Salim Mansyur; Ruminda Ruminda (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
respect others' faces. This research aimed to find out the impoliteness strategies in the YouTube comment section of Rishi Sunak regarding the National Health Service. Culpeper's (1996) impoliteness strategies theory was employed to answer the research question. Furthermore, a qualitative method and a pragmatic approach were employed in this research. According to the findings of this research, there were 58 impoliteness strategies discovered within the 54 data analyzed, with 4 data having more than one strategy. There were 4 occurrences of bald on record impoliteness strategies, 19 occurrences of positive impoliteness strategies, 34 occurrences of negative impoliteness strategies, and 1 occurrence of sarcasm or mock politeness strategy. Impoliteness strategies that most frequently occur was negative impoliteness. Meanwhile, impoliteness strategy that was absent was withhold politeness.